The impact of applying environmental management standards in achieving sustainable development: evidence from food product manufacturing companies in Saudi Arabia - Fuad Mohammed Alhamdi; Shaker M. Al-Kahtani (Discover Sustainability)
Abstract This study explores the impact of environmental management standards specifically ISO 14000, green production, and environmental policies on sustainable development within food manufacturing companies in Saudi Arabia. It also investigates the moderating role of environmental management on these relationships. A questionnaire was distributed to 370 participants across various management levels, with data analyzed using structural equation modeling (SEM) via SmartPLS 4. The findings reveal that ISO 14000, green production, environmental policies, and environmental management each have significant positive effects on sustainable development. However, environmental management negatively moderates the relationship between ISO 14000 and sustainable development and does not significantly influence the moderating effects of green production or environmental policies. The study offers practical recommendations to enhance sustainability performance through these standards and highlights opportunities for future research and practical advancements in the sector.